Isu Ketuhanan dalam Bicara Falsafah - Abdul Mukti, Mohd Fakhrudin (Jurnal Usuluddin, 1999)
Naturally, human being will recognise that there is God. It is because all the created things one perceives in his or her life are the actual signs of God's existence. God's existence began to be treated philosophically by the philosophers from the Greek until today. The intellect alone becomes a means in their attempts to know God who is very significant and mysterious. The concept of God was discussed by the modern and the contemporary philosophers on the basis of their intellects and perceptions. Therefore, they mostly tried to establish the truth that based on the practical sciences and materialism. But when Islam came, the source of knowing God was confined to the revelation which defined the absolute reality of God. Thus, the Muslim philosophers seemed to master the discussion on this issue referring to both the Qur'an and intellect trying to establish the fact that Islam is the religion of intellect. The matter is no longer whether there is God or not, or perhaps God's attributes are Himself or superadded to Him as dramatically discussed in so far but now, Islamically, how to understand God correctly - as we can - and to try to contribute to present Islam to the world as it is.